Virtual Laboratory-Based Inquiry Restoration: Anderson's Knowledge Dimension Assessment - Tawil, Muh; Yanto, Nurfitra (LPPM STKIP Kusuma Negara, 2025)
This study assesses the Virtual Laboratory-Based Inquiry Restoration (VLab-InR) model's effectiveness in enhancing students’ factual and procedural knowledge. Developed as a virtual science lab alternative, especially useful during COVID-19 restrictions, the model structures science experiments in a digital environment. A quasi-experimental design with 42 students in two non-randomized groups, A and B, was employed. Pre- and post-assessments measured knowledge gains, and a questionnaire gauged student response. Data analysis using an independent t-test showed significant improvements, with a moderate normalized gain in both groups. Group A had a higher average increase than Group B. Students rated VLab-InR positively, with an approval average of 91.58%. Findings suggest VLab-InR effectively enhances factual and procedural knowledge and fosters critical thinking through virtual simulations, offering a practical solution for science learning in the digital age.